Evaluation of Acute Toxicity of Ethanolic Extract from Fruit of Cyanometra cauliflora in ICR Mice - Somsap, On-Anong; Payanglee, Kolip; Kamnate, Anussara; Singdam, Patcharin (Trends in Sciences, 2024)
This research aims to investigate the acute toxicity profile of the ethanolic extract derived from Cyanometra cauliflora fruit, a plant commonly found in Southeast Asia. Male ICR mice were divided into 5 groups and administered varying oral doses of C. cauliflora extract: 100, 200 and 400 mg/kg body weight. Subsequently, the effects on both histological and biochemical parameters were meticulously examined post-experimentation. The results indicated no significant alterations in blood glucose or blood urea nitrogen (BUN) levels attributable to C. cauliflora extract administration. Nevertheless, a noteworthy elevation in creatinine, aspartate transaminase (AST), and alkaline phosphatase (ALP) levels was observed across all groups treated with C. cauliflora extract in comparison to controls (p < 0.05). Intriguingly, the extract consistently elicited a reduction in triglyceride levels across all administered doses, while cholesterol levels exhibited a decline specifically at the 400 mg/kg body weight dose. Notably, the levels of low-density lipoprotein (LDL) and high-density lipoprotein (HDL) remained unaltered throughout the experimentation. Histological assay suggested signs of hepatocellular damage, portal dilation and infiltration of inflammatory cells across all C. cauliflora-treated groups, alongside indications of kidney atrophy and other abnormalities. These findings collectively suggest structural and functional modifications induced by C. cauliflora extract. In summary, while the administration of C. cauliflora extract did not exert significant changes in blood glucose and BUN levels, it did lead to heightened levels of creatinine and liver enzyme markers. Furthermore, liver and kidney damage were discerned at doses ranging from 100 to 400 mg/kg body weight, underscoring the imperative need to optimize extract concentrations to mitigate potential cytotoxic effects. These findings can be further explored to understand the processes behind the observed effects and to assess potential therapeutic applications or safety considerations associated with the use of C. cauliflora extract in clinical settings. HIGHLIGHTS A hepatic and renal toxicity profile was detected in the ethanolic fruit extract of Cyanometra cauliflora, despite the absence of fatalities. The ethanolic fruit extract of cauliflora L. lowered cholesterol and triglyceride levels. Prolonged ingestion could be detrimental. GRAPHICAL ABSTRACT